The Effectiveness Of Training In Early Detection Of Cervical Cancer And Breast Cancer At Bapelkes Cikarang Increasing IVA Examination Coverage In Bekasi City - Melania Eriyani; Mustopa, Mustopa (Jurnal EduHealth, 2024)
The IVA examination coverage rate in Bekasi City is still low, indicating problems of increasing competence. This competency is enhanced through training in early detection of cervical and breast cancer. This study aims to determine the effectiveness of early detection training for cervical cancer and breast cancer for doctors and midwives in increasing the coverage of IVA examinations in Bekasi City. The quantitative approach was applied in this research through a quasi-experimental research design. The population used was all community health centers in Bekasi City, while the sampling technique used was a saturated sampling technique, namely taking all existing samples. Variables are measured using a quantitative questionnaire that has been standarized. This quantitative data analysis uses the SPSS version 18. Quantitative data analysis includes univariate and bivariate analysis. The results of the study showed that there were differences in knowledge, attitudes and behavior between the control group and the intervention group. Increased IVA coverage in the intervention group after being given early detection training.Early detection training is considered effective because there is an increase in knowledge, attitudes and behavior as well as coverage of IVA in Bekasi City. Future research can measure more comprehensively the effectiveness of training in terms of programs in the health service